Descripción de los pulsos de ecolocalización de once especies de murciélagos insectívoros aéreos de una selva baja caducifolia en Morelos, México - Orozco-Lugo, Lorena; Guillén-Servent, Antonio; Valenzuela-Galván, David; Arita, Héctor T. (THERYA, 2013)
Echolocation calls for insectivorous bats vary within species; therefore a description for each locality of study is needed to allow species identification. We present here description of the echolocation calls for eleven aerial insectivorous bat species from a tropical dry forest in Morelos, México. The ultrasound sequences were recorded in time expansion mode (10x) using Pettersson Elektronik ultrasound detectors. Bat calls recorded, were analyzed using BatSound 1.10 software. Initial and final frequency, frequency of maximum amplitude, pulse length, pulse interval and number of harmonics for pulses from the search phase, were measured. Data were averaged and compared with published data for other localities. At our study site, insectivorous bats from the Molossidae and Mormoopidae families, and the bat Balantiopteryx plicata, are easily identifiable based in the quantitative and qualitative characteristics of their calls. The characteristics that presented more variation related to previous descriptions for other localities were the pulse duration and the frequencies, not the arrangement of the components of constant or modulated frequency. Asides, the extent of this variation is bigger for localities far apart. Key words: acoustic detection, chiroptera, dry forest, Sierra de Huautla, ultrasounds.